Towards the Formulation of a Proposal for Opportunity-to-Learn Standards - Cárdenas Ramos, Rosalba; Hernández Gaviria, Fanny (Íkala, Revista de Lenguaje y Cultura, 2011)
This paper focuses on the need to formulate and implement a proposal for opportunity-to-learn standards (OTL) in the field of language learning and teaching in Colombia, with the aim of ensuring the necessary conditions for the implementation and achievement of the performance standards, issued by the Ministry of Education as part of the National Bilingual Program in this area. First, it reviews the concept, origins, composition and models of OTL standards, and then it examines the Colombian situation to make a case for OTL in this country.